2017
DOI: 10.1021/acs.energyfuels.6b02324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Thermochemistry of Coal Char Oxidation and Desorption of Surface Oxides

Abstract: The present study investigates the coal char combustion by a combination of thermochemical and X-ray photoemission spectroscopy (XPS) analyses. Thermoanalytical methods (differential thermogravimetry, differential scanning calorimetry, and temperature-programmed desorption) are used to identify the key reactive steps that occur upon oxidation and heating of coal char (chemisorption, structural rearrangement and switchover of surface oxides, and desorption) and their energetics. XPS is used to reveal the chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…demonstrated that a further increase in the oxidation temperature results in the creation of other surface oxides, including epoxy, ether, and carbonyl–carboxyl groups. The same group of researchers analyzed preoxidized samples, noting that epoxy structures are metastable but, at high temperatures, transform into the “edge” groups, namely, the carbonyl–carboxyl and ether groups . When those preoxidized samples were heated in N 2 , the oxide species desorbed as CO and CO 2 .…”
Section: New Research Frontiersmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that a further increase in the oxidation temperature results in the creation of other surface oxides, including epoxy, ether, and carbonyl–carboxyl groups. The same group of researchers analyzed preoxidized samples, noting that epoxy structures are metastable but, at high temperatures, transform into the “edge” groups, namely, the carbonyl–carboxyl and ether groups . When those preoxidized samples were heated in N 2 , the oxide species desorbed as CO and CO 2 .…”
Section: New Research Frontiersmentioning
confidence: 99%
“…The same group of researchers analyzed preoxidized samples, noting that epoxy structures are metastable but, at high temperatures, transform into the "edge" groups, namely, the carbonyl−carboxyl and ether groups. 296 When those preoxidized samples were heated in N 2 , the oxide species desorbed as CO and CO 2 . 150 The CO/CO 2 ratio increased with the temperature of preoxidation, correlating with a higher ratio of edge to epoxy groups.…”
Section: New Research Frontiersmentioning
confidence: 99%
“…Notably this technique may underestimate the total amount of OFGs as only acidic and basic groups are accounted for, whereas the neutral ether and carbonyl groups cannot be detected . More recently, indeed, X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD) have been used to investigate OFGs present on carbon materials. , Recently, some experimental works have tried to combine the analysis of the carbon surface by XPS with thermoanalytical techniques (TPD and differential scanning calorimetry (DSC)) in order to investigate the thermochemistry of the main steps of the carbon–oxygen reaction in combustion processes. Levi et al and Cerciello et al within the theoretical frame of the three-step semilumped kinetic model of coal combustion proposed by Hurt and Niksa , suggested that the overall thermicity of a carbon–oxygen reaction results from the sum of exothermic (chemisorption and surface oxide rearrangement) and endothermic (CO x abstraction) steps .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, indeed, X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD) have been used to investigate OFGs present on carbon materials. , Recently, some experimental works have tried to combine the analysis of the carbon surface by XPS with thermoanalytical techniques (TPD and differential scanning calorimetry (DSC)) in order to investigate the thermochemistry of the main steps of the carbon–oxygen reaction in combustion processes. Levi et al and Cerciello et al within the theoretical frame of the three-step semilumped kinetic model of coal combustion proposed by Hurt and Niksa , suggested that the overall thermicity of a carbon–oxygen reaction results from the sum of exothermic (chemisorption and surface oxide rearrangement) and endothermic (CO x abstraction) steps . Accordingly, while the overall combustion heat would be always exothermic, the heat registered in a TPD step could be either endo- or exothermic depending on the operating temperature, as it results from the balance of the exothermic stabilization of metastable oxides and the endothermic desorption of CO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation